Influence of the metabolic inhibitor sesamin on the fatty acid profile of the oleaginous yeast Rhodotorula glutinis - Holmgren, Louise (2014)
Rhodotorula glutinis has been one of the top candidates among oleaginous yeast for several microbial lipid applications, such as biofuel production. In this project the effect of sesamin on the fatty acid profile was investigated by culturing R.glutinis J195 with low nitrogen and high carbon cultures with DMSO as the solvent of sesamin, firstly in baffled flasks and thereafter in fermenters. Glucose consumption, biomass accumulation, lipid content and lipid composition were determined. Sesamin had effect on the fatty acid profile by lowering the amount of several fatty acids as well as increasing others. There was neither decrease in biomass accumulation nor change in the pattern of glucose consumption by addition of sesamin. The most encouraging result was the slight increase of docosahexaenoic acid (22:6n-3),which is a polyunsaturated fatty acid that is regarded as one of the health beneficial ω3 fatty acids found in fish. However the results are obscure due to different sample treatments and impure lipid samples as well as that the fatty acid standard seemingly had oxidised.